2010
DOI: 10.7589/0090-3558-46.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Avian Paramyxoviruses in Shorebirds and Gulls

Abstract: ABSTRACT:There are nine serotypes of avian paramyxovirus (APMV), including APMV-1, or Newcastle disease virus. Although free-flying ducks and geese have been extensively monitored for APMV, limited information is available for species in the order Charadriiformes. From 2000 to 2005 we tested cloacal swabs from 9,128 shorebirds and gulls (33 species, five families) captured in 10 states within the USA and in three countries in the Caribbean and South America. Avian paramyxoviruses were isolated from 60 (0.7%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
3
21
0
Order By: Relevance
“…In contrast to this, we did not isolate any APMV during the spring migration, nesting, and after nesting movements. In general, these rates are similar to data of other authors (45)(46)(47) and might be associated with environmental and biological characteristics of the life cycle of birds, especially migratory and wintering strategies. As is known, autumn migration of wild waterfowl occurs more slowly, when the local moving is gradually turning into migration (52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast to this, we did not isolate any APMV during the spring migration, nesting, and after nesting movements. In general, these rates are similar to data of other authors (45)(46)(47) and might be associated with environmental and biological characteristics of the life cycle of birds, especially migratory and wintering strategies. As is known, autumn migration of wild waterfowl occurs more slowly, when the local moving is gradually turning into migration (52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 75%
“…Addition- ally, all 4 viruses were isolated in the same geographic location and in a short period of time according to our observations of the same bird populations. Other authors have reported APMV-2 isolation from dunlins (46). In North America, the prevalence of APMV-1 infections among dunlins was 0.5%.…”
Section: Discussionmentioning
confidence: 96%
“…We also question genus classifications for several viruses, including viruses #111 (Avian paramyxovirus 6), #1521 (Sendai virus), #1355 (Porcine rubulavirus). The authors [34][36] make these classification decisions by analyzing specific gene coding regions or protein sequences, while our natural vector uses the global sequence information of genomes. Furthermore, for genera Ephemerovirus and Jeilongvirus , we question their family classifications provided by ICTV because they are closer to other families ( Jeilongvirus to family Filoviridae and Ephemerovirus to family Paramyxoviridae ) based on our graphical representation.…”
Section: Resultsmentioning
confidence: 99%
“…Coronaviruses (COV), paramyxoviruses (PMV), and influenza A viruses (IAV) have been detected in a large diversity of wild bird species (e.g., Stallknecht and Shane, 1988;Coffee et al, 2010;Muradrasoli et al, 2010). In seabirds, COV, PMV, and IAV infections are commonly reported in species in the order Charadriiformes (gulls, terns, shorebirds).…”
mentioning
confidence: 99%